2008
DOI: 10.1289/ehp.10963
|View full text |Cite
|
Sign up to set email alerts
|

Road Proximity Increases Risk of Skeletal Abnormalities in Wood Frogs from National Wildlife Refuges in Alaska

Abstract: BackgroundSkeletal and eye abnormalities in amphibians are not well understood, and they appear to be increasing while global populations decline. Here, we present the first study of amphibian abnormalities in Alaska.ObjectiveIn this study we investigated the relationship between anthropogenic influences and the probability of skeletal and eye abnormalities in Alaskan wood frogs (Rana sylvatica).MethodsFrom 2000 to 2006, we examined 9,269 metamorphic wood frogs from 86 breeding sites on five National Wildlife … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 34 publications
2
47
2
1
Order By: Relevance
“…Our prior studies (Reeves et al 2008 suggested two different hypotheses regarding how copper and predators may interact to produce abnormal frogs in nature, and we found evidence to support only one of these in this experiment. Even the relatively low Cu concentrations in some high malformation sites may be toxic enough to reduce tadpole activity enough to inhibit feeding, which could lead to smaller size over a growing season or a longer duration of exposure to gape-limited predators, like dragonfly larvae.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Our prior studies (Reeves et al 2008 suggested two different hypotheses regarding how copper and predators may interact to produce abnormal frogs in nature, and we found evidence to support only one of these in this experiment. Even the relatively low Cu concentrations in some high malformation sites may be toxic enough to reduce tadpole activity enough to inhibit feeding, which could lead to smaller size over a growing season or a longer duration of exposure to gape-limited predators, like dragonfly larvae.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, despite our observation that smaller frogs are more likely to be abnormal (Reeves et al 2008), we do not know whether frogs are small because they are abnormal or whether something about being small makes tadpoles more likely to become abnormal. These size differences are nontrivial: metamorphs in areas with few abnormalities (like remote areas of the Arctic Refuge) are 21% larger on average (mean snout to vent length (l SVL ) ¼ 23 mm, N ¼ 616) than metamorphs in areas where abnormalities are more frequent (Kenai NWR l SVL ¼ 19 mm, N ¼ 5,716; Reeves et al 2008). There is a need to understand how chemicals and predators interact to influence frog abnormalities in order to manage ecosystems to limit their occurrence.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Even if we consider that the increasing number of reports may not be linked to a higher frequency of malformation occurrences, an increment in the stressors seems to be occurring in nature. Ubiquitous stressors like UV-B radiation, ground-level ozone, acid precipitation and extreme temperatures, as well as products of anthropogenic activities such as chemical contaminants and radioactive mineral deposits, and even proximity to roads (Reeves et al, 2008) are considered to play a role in the appearance of morphological abnormalities.…”
mentioning
confidence: 99%